A Rare Case of Spontaneous Hemorrhage in a Giant Accessory Spleen in a Child. (20th January 2019) - Grilli, Gianpaolo; Pastore, Valentina; Bertozzi, Vincenzo; Cintoli, Annarita Nunzia; Perfetto, Francesco; Nobili, Maria; Canale, Francesco; Macarini, Luca
Abstract : Accessory spleen (AS) is a condition found in about 20% of patients and is most commonly located in the hilar region of the spleen. It is more often asymptomatic, single, and smaller than 2 cm. In the present study, we report the rare case of a 13-year-old boy with giant accessory spleen underwent spontaneous intrasplenic hemorrhage who presented with recurrent abdominal pain. Contrast-enhanced MRI was mandatory for the diagnosis before surgical procedure.